1999
DOI: 10.1128/aem.65.2.822-827.1999
|View full text |Cite
|
Sign up to set email alerts
|

Poly-3-Hydroxybutyrate in Legionella pneumophila , an Energy Source for Survival in Low-Nutrient Environments

Abstract: Chloroform-soluble material was extracted from two strains ofL. pneumophila serogroup 1 following growth in continuous culture. The purified material was identified as poly-3-hydroxybutyrate (PHB) by nuclear magnetic resonance spectroscopy and by gas chromatography-mass spectrometry. PHB yields of up to 16% of cell dry weight were extracted from culture samples. The PHB was located in electron-dense intracellular inclusions, which fluoresced bright yellow when stained with the lipophilic dye Nile red. A Nile r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(62 citation statements)
references
References 48 publications
0
61
0
1
Order By: Relevance
“…In dd water, L. pneumophila was unable to metabolize its inclusions of poly-β-hydroxybutyrate (PHB) and lost its culturability much faster than in tap water, suggesting that during starvation, culturability is extended at the expense of PHB. In fact, depletion of PHB and loss of culturability correlate in starved L. pneumophila (James et al, 1999). In general, the presence of PHB in starved bacteria extends metabolic processes, correlates with reduced degradation of RNA and proteins, and provides a direct carbon and energy source, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dd water, L. pneumophila was unable to metabolize its inclusions of poly-β-hydroxybutyrate (PHB) and lost its culturability much faster than in tap water, suggesting that during starvation, culturability is extended at the expense of PHB. In fact, depletion of PHB and loss of culturability correlate in starved L. pneumophila (James et al, 1999). In general, the presence of PHB in starved bacteria extends metabolic processes, correlates with reduced degradation of RNA and proteins, and provides a direct carbon and energy source, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…MIFs show prominent cytoplasmic inclusions and are motile and highly infectious to cultured cells . L. pneumophila inclusions consist of poly-β-hydoxybutyrate, as determined by nuclear magnetic resonance, gas chromatography and mass spectrometry (James et al, 1999). The inclusions become fluorescent after staining with Nile red and are consumed during starvation (as determined by fluorometry and fluorescence microscopy), suggesting that they constitute a nutritional reserve (James et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Under inanition, bacteria may remain viable for a long time if appropriate intracellular endogenous reserves are available (Kolter et al 1993;Ruiz et al 2001). Poly-b-hydroxyalkanoate (PHA) is an intracellular storage form of carbon and energy in bacterial cells (Lee 1996) and provides carbon and energy during starvation (James et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, Legionella accumulates PHB granules as an endogenous reserve of energy (29). For bacteria other than Legionella, it has also been demonstrated that BdhA is one of the enzymes of the metabolism of PHB, involved in the first step of the degradation process (28).…”
Section: Microscope Observation Of Phb Granulesmentioning
confidence: 62%